Implementasi Media Pembelajaran Canva dalam Meningkatkan Hasil Belajar Siswa Kelas VII pada Materi Sholat dan Dzikir di SMP Negeri 2 Kabuh - Nuraini, Laila Dwi; Wahyudi, Wahyudi (Lembaga Yasin AlSys, 2025)
This study is motivated by the scarcity of research on the use of digital learning media such as Canva in Islamic Religious Education, particularly for topics that are difficult for students to understand, such as Sholat and Dzikir. The research aims to examine the implementation of Canva as a learning medium to improve the learning outcomes of Grade VII students at SMP Negeri 2 Kabuh and to identify its supporting and inhibiting factors. A descriptive qualitative approach was employed, with Grade VII students selected purposively as the study subjects. Data were collected through observation, interviews, documentation, and pretest–posttest assessments as supporting data, then analyzed using an interactive analysis technique comprising data reduction, data presentation, and conclusion drawing. The findings show that the use of Canva enhanced students’ understanding, motivated learning, and created an interactive and enjoyable learning environment. The improvement in posttest scores compared to pretest scores indicates a positive effect on learning outcomes. These findings reinforce visual and multimodal learning theories and highlight the importance of interactive media in education. In conclusion, Canva is effective in improving learning outcomes when supported by teacher training and adequate facilities. The study’s implications include strengthening the theoretical basis for using digital media in religious education and providing practical recommendations for teachers and schools to sustainably optimize Canva, as well as opening opportunities for further research on other digital media in Islamic Religious Education across different educational levels.